Woody species of the Miombo woodlands and geoxylic grasslands of the Cusseque area, south-central Angola - Rasmus Revermann; Francisco Gonçalves; Amândio Gomes; Manfred Finckh (Check List, 2017)
The species composition of the vegetation in most regions of Angola has been poorly studied and most studies date back to the pre-independence era. In this study, we provide a detailed account of the woody flora of the Miombo woodlands and geoxylic grasslands of the Cusseque study site of “The Future Okavango” (TFO) project, situated on the Angolan Central Plateau. The checklist is based on a vegetation survey using vegetation plots of 1,000 m² and also includes records from botanical collections made elsewhere at the study site. In total, we documented 154 woody species belonging to 99 genera of 37 plant families in 100 km². The study represents the first comprehensive account of the woody vegetation of the area including all habitats and growth forms.